Size Dependence of [n]Cycloparaphenylenes (n=5–12) in Electrochemical Oxidation. Issue 12 (2nd June 2016) - Kayahara, Eiichi; Fukayama, Kei; Nishinaga, Tohru; Yamago, Shigeru
Abstract: The oxidation processes of [ n ]cycloparaphenylenes ([ n ]CPPs) ( n =5–12) were systematically investigated by cyclic and rotating disk electrode voltammetry. All CPPs underwent pseudo‐reversible two‐electron oxidation irrespective of ring size, forming the corresponding radical cations and then dications. The results were in sharp contrast to those observed for linear oligoparaphenylenes, which only undergo one‐electron oxidation. The difference in the first and second oxidation potentials in the CPP oxidation was affected by the ring size and became more significant as the decrease of CPP size. In other words, while the first oxidation from neutral CPP to the radical cation occurred faster as the size of CPP becomes smaller, the second oxidation from the radical cation to dication exhibited opposite size dependence. Abstract : Two electrons worth : The oxidation processes of [ n ]cycloparaphenylenes ([ n ]CPPs) ( n =5–12) were systematically investigated by cyclic and rotating disk electrode voltammetry. All CPPs underwent pseudo‐reversible two‐electron oxidation irrespective of ring size, forming the corresponding radical cations and then dications. The difference in the first and second oxidation potentials in the CPP oxidation was affected by the ring size and became more significant as the decrease of CPP size.